2020
DOI: 10.1007/s43939-020-00001-9
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of molecular mechanisms of carbonate biomineralization by bacteria

Abstract: Although biomineralization of CaCO3 is widespread in Bacteria and Archaea, the molecular mechanisms involved in this process remain less known than those used by Eukaryotes. A better understanding of these mechanisms is crucial for a broad diversity of studies including those (i) aiming at assessing the role of bacteria in the geochemical cycles of Ca and C, (ii) investigating the process of fossilization, and (iii) engineering applications using bacterially mediated CaCO3 mineralization. Different types of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 170 publications
(240 reference statements)
0
84
0
Order By: Relevance
“…Consistently with a pH buffer role, ACC inclusions precipitate when cells oxidize sulfide to S 0 and dissolve when cells are exposed to O 2 and S 0 is oxidized to sulfate [Yang et al, 2019]. Similarly, photosynthesizing bacteria tend to consume protons when fixing CO 2 by RuBisCO and formation of ACC may contribute to pH buffering in addition to other molecular pH-buffering systems such as proton pumps [Görgen et al, 2021]. (iii) Last, it has been suggested that ACC inclusions, owing to their density (>2 g•cm −3 ), serve as ballasts for cells, and thus represent an adaptation to a benthic lifestyle [Couradeau et al, 2012, Gray and Head, 2014.…”
Section: Intracellular Carbonates: a Controlled Biomineralization Process With Unidentified Functionsmentioning
confidence: 82%
See 2 more Smart Citations
“…Consistently with a pH buffer role, ACC inclusions precipitate when cells oxidize sulfide to S 0 and dissolve when cells are exposed to O 2 and S 0 is oxidized to sulfate [Yang et al, 2019]. Similarly, photosynthesizing bacteria tend to consume protons when fixing CO 2 by RuBisCO and formation of ACC may contribute to pH buffering in addition to other molecular pH-buffering systems such as proton pumps [Görgen et al, 2021]. (iii) Last, it has been suggested that ACC inclusions, owing to their density (>2 g•cm −3 ), serve as ballasts for cells, and thus represent an adaptation to a benthic lifestyle [Couradeau et al, 2012, Gray and Head, 2014.…”
Section: Intracellular Carbonates: a Controlled Biomineralization Process With Unidentified Functionsmentioning
confidence: 82%
“…The primary driver for calcification in biofilms is the local increase in calcium carbonate supersaturation, which may result from specific microbial metabolisms, for instance, photosynthesis, ureolysis, or sulfate reduction [e.g., Saghaï et al, 2016, White et al, 2016. This active, biologically induced CaCO 3 mineralization process occurs concurrently with passive binding of Ca 2+ ions on the EPS matrix of the biofilm, which may favor CaCO 3 heterogeneous nucleation, and influence mineral properties such as morphology, size, or structure [Dupraz et al, 2009, Görgen et al, 2021, Lyu et al, 2020. Interestingly, it is now recognized that microbially induced CaCO 3 precipitation may not be limited to heavily calcifying, mat-building environmental communities such as those forming stromatolites, but can also occur in biofilms of bacteria previously studied as pathogens in a medical context [e.g., Pseudomonas aeruginosa or Proteus mirabilis; Li et al, 2016aLi et al, , 2015.…”
Section: Biominerals and Biofilm Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…Microbially induced calcium carbonate precipitation has been widely reported in the biosphere, as a result of interaction between biological activities and the environment. [10][11][12][13] It has been reported that different microorganisms were involved in carbonate biomineralization, with different functions. [14][15][16][17] For example, Chlorella spirulina and Spirulina platensis induced calcite precipitation by xing CO 2 /HCO 3 À , and Spirulina platensis had higher calcite deposition rate than Chlorella spirulina.…”
Section: Introductionmentioning
confidence: 99%
“…The end product (the biomineral) of BCM serves a biological function for its host. Some notable examples include magnetotactic bacteria (the magnetite chain helps target microaerophilic environments) and bacteria that biomineralize carbonates (intracellular carbonate contributes to buoyant density) (Uebe and Schüler, 2016 ; Görgen et al, 2021 ). Conversely, mineral formation in BIM does not have a regulatory control and the biomineralization product is generally located outside the cell.…”
mentioning
confidence: 99%